Talagha: Marketing Communications for Integrated Coastal Tourism Branding - Yuliana Rakhmawati; Qoniah Nur Wijayani; Diah Indiyati; Evi Novianti (ETTISAL : Journal of Communication, 2023)
Madura has beach comparative potential as a coastal tourist destination. However, in the marketing communications context, this potential has not been optimized. Therefore, this research aims to explore all the potential for integrated coastal tourism by using the Talagha acronym of Talang Siring, Legend, Jumiang, and Lembung branding identity as an alternative to marketing communication. The Talagha brand identity not only being as destinations acronym but also the equivalent of lake in Madurese. Research locations were conducted on four Pamekasan coastal tourism destinations in Madura, namely Talang Siring Beach, Jumiang Beach, Legend Beach, and Mangruve Lembung. Research population are visitors and residents around the destinations. Samples were obtained using accidental sampling. Based on target population characteristics, as two hundres samples were acquired. Data collection were conducted by survey and analyzed by using SPSS. The results show that Talagha tagline as a brand identity is agreed by majority respondents to be part of integrated tourism branding. The findings confirmed by branding strategies theory as a part of tourist destination marketing communications. This findings are expected to be a catalyst in brand identity usage in tourist destination marketing communications development. It is recommended these findings as literature in brand destination studies as well as reaches triple helix in developing policies brief related to Madura’s integrated coastal tourism branding.